1995
DOI: 10.1007/bf02190737
|View full text |Cite
|
Sign up to set email alerts
|

Early parental loss and depressive disorder in Japan

Abstract: The aim of this study is to determine in a Japanese sample whether or not the permanent loss of a parent by death or separation in childhood is aetiologically associated with unipolar major depressive disorder (according to RDC). We compared the incidence of parental loss before 17 years of age by death or separation between 122 depressed inpatients and 94 non- and never-depressed medical controls. Early maternal death was found to be significantly more common in the depressives than in the controls. Separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
26
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
6
26
0
1
Order By: Relevance
“…It has been reported that girls are more vulnerable to develop depression after parental loss than boys (Kunugi et al, 1995). Because the neuroendocrine stress response is subject to sex differences (Rhodes and Rubin, 1999), one might speculate that differential disease risk after ELE might be associated with different neuroendocrine consequences of ELE in boys and girls.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that girls are more vulnerable to develop depression after parental loss than boys (Kunugi et al, 1995). Because the neuroendocrine stress response is subject to sex differences (Rhodes and Rubin, 1999), one might speculate that differential disease risk after ELE might be associated with different neuroendocrine consequences of ELE in boys and girls.…”
Section: Introductionmentioning
confidence: 99%
“…More rigorous comparisons with medical controls have tended not to find a significant difference, [16][17][18] with exceptions. 19 Lack of association of death of a parent in childhood with adult depression is particularly true of studies which employed an epidemiological approach. [20][21][22] (2) Differences between depressed patients and controls with regard to separation experiences (of variable length) have tended to become more definitive as the methodological rigor of case control studies has increased 18,23 and are a relatively consistent finding in epidemiologically based samples.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] (2) Differences between depressed patients and controls with regard to separation experiences (of variable length) have tended to become more definitive as the methodological rigor of case control studies has increased 18,23 and are a relatively consistent finding in epidemiologically based samples. [20][21][22] (3) There is a trend for loss of mother to be more associated with depression than loss of father, 19,24 but this finding is not consistent. 20,23 (4) Loss in early childhood has been reported to be of greater pathogenic significance than loss in later childhood and adolescence 24,25 but this was not observed in all studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews conducted in the late 80s concluded that, although there is no evidence that parental death is a significant risk factor for depression, separations, particularly those occurring in the context of family discord, seem to contribute to adult depression (Brown et al, 1986;Tennant, 1988). Studies based on patients who were hospitalized for severe depression and/or attempted suicide have found a higher prevalence of parental death among severe depressed subjects than in the general population (Kunugi et al, 1995;Munro, 1966).…”
mentioning
confidence: 99%